2018
DOI: 10.1037/lat0000083
|View full text |Cite
|
Sign up to set email alerts
|

Mexican-origin husbands’ work contexts and spouses’ marital quality.

Abstract: Relative to other men, Latino immigrant men are disproportionately likely to experience challenging working conditions, including too many or too few hours, discrimination, and job (in)security. Previous research suggests that work contexts (particularly husbands') may affect interactions between family members, which in turn, spill over into family functioning. The present study examined the patterning of 118 Mexican husbands' self-reported workplace characteristics (i.e., job security, workplace discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Contemporary qualitative studies of Latino and Mexican-origin families offer some insights into why this may be so (e.g., Hirsch, 2003;Parra-Cardona et al, 2008). Therefore, dissonance between spouses' gender role attitudes and wives' employment may be normative in the context of immigration and correspondingly less salient to spouses' perceptions of marital warmth and connection (Hengstebeck, Helms, Wood, & Rodriguez, 2017). Therefore, dissonance between spouses' gender role attitudes and wives' employment may be normative in the context of immigration and correspondingly less salient to spouses' perceptions of marital warmth and connection (Hengstebeck, Helms, Wood, & Rodriguez, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary qualitative studies of Latino and Mexican-origin families offer some insights into why this may be so (e.g., Hirsch, 2003;Parra-Cardona et al, 2008). Therefore, dissonance between spouses' gender role attitudes and wives' employment may be normative in the context of immigration and correspondingly less salient to spouses' perceptions of marital warmth and connection (Hengstebeck, Helms, Wood, & Rodriguez, 2017). Therefore, dissonance between spouses' gender role attitudes and wives' employment may be normative in the context of immigration and correspondingly less salient to spouses' perceptions of marital warmth and connection (Hengstebeck, Helms, Wood, & Rodriguez, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given the structural constraints associated with cultural adaptation that make wives' employment and/or husbands' overwork necessary for many Mexican immigrant families (Updegraff, Crouter, Umaña-Taylor, & Cansler, 2007), expectations regarding women's roles in their families are often redefined to include wives' employment (Baker, 2004;Esteinou, 2007). Therefore, dissonance between spouses' gender role attitudes and wives' employment may be normative in the context of immigration and correspondingly less salient to spouses' perceptions of marital warmth and connection (Hengstebeck, Helms, Wood, & Rodriguez, 2017). Thus, regardless of wives' employment status, spouses' beliefs in patriarchal marital roles may reduce the capacity for connection in marriage, whereas partners' flexibility in gender role attitudes may serve as a resource for fostering warmth during the process of immigration.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) found associations between discrimination and family strain, which was subsequently linked to disease activity via individuals' stress reactivity for African American participants in the Midlife in the U.S. (MIDUS) study (Ryff, Almeida, Ayanian, et al., 2017). In other prior research, Mexican American men with greater exposure to ethnic discrimination at work demonstrated less warmth to their wives when compared to men in secure, and positive work environments (Hengstebeck et al., 2018), and among Asian Americans, 40% of the association between perceived discrimination and psychological distress was conveyed by family strain, especially family conflict, in this group (Kwon, 2020).…”
Section: Introductionmentioning
confidence: 65%
“…One explanation for immigrants' high rates of martial dissatisfaction and dissolution is stress associated with spousal differences in adaptation. Cultural adaptation includes a wide spectrum of attitudinal and behavioral changes (Knight et al, 2018), and immigrant husbands and wives might adapt at different rates to various cultural domains (i.e., language, cultural values; Grzywacz et al, 2009;Hengstebeck et al, 2018). Disagreements in values and expectations may arise within dyads and compromise people's ability to maintain strong relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Mexican-origin couples who match at, for example, low levels of cultural adaptation may experience different sources of adaptation stress than couples who match at high levels of adaptation, which may influence marital dissatisfaction. At the same time, it is also possible that husbands and wives differ from each other in their workplace experiences and lengths of stay in the United States (Grzywacz et al, 2009;Hengstebeck et al, 2018); thus, husbands and wives may also differ in their rates of adopting, and maintaining, their American versus Mexican orientations, which could manifest in spousal mismatches in adaptation. Specifically, we argue that (1) level of acculturation matching (e.g., high-high vs. low-low) and (2) mismatches between Mexican-origin husband and wives' levels of cultural adaptation (e.g., high-low vs. low-high) may have important implications for their marital quality.…”
Section: Introductionmentioning
confidence: 99%